Land Use Change and Surface Water Runoff Dynamics of Chattogram Metropolitan Area - Islam, Md. Saimun; Nahrin, Kasphia (The Jahangirnagar Review, 2025)
Urbanization-driven land use cover changes significantly affect hydrological processes. This can alter the surface water runoff patterns. This research explores the relationship between land use changes and surface runoff water issues focusing on the study city Chattogram Metropolitan Area (CMA), the most significant port city in Bangladesh. The rapid urban development in Chattogram causes increased incidents and severity levels of waterlogging and urban flood in several parts of the city. The decadal Land Use and Land Cover (LULC) change was analyzed by supervised image classification of twenty years’ (from 2003 to 2023) Landsat time-series data. It was determined considering five land use classes: agriculture, buildup area, bare land, vegetation, and waterbody classes. The Natural Resources Conservation Service (NRCS) curve number method was also applied to estimate the surface runoff water. The research found that, the LULC has significantly decreased in waterbodies by 30.29%, vegetated areas by 30.29%, and agriculture by 12.09% in the CMA. The buildup area, on the other hand, has been reflected to have the biggest shift, increasing by 55.99%. The estimated surface runoff has likewise experienced a sharp change, rising from 1.25 km2 of high runoff in 2003 to 272.92 km2 in 2013 and 419.00 km2 of very high runoff in 2023. Pearson correlation analysis shows a consistently strong and highly significant positive correlation between LULC and surface runoff. This emphasizes the influential role of LULC dynamics in shaping hydrological patterns in CMA.